2021
DOI: 10.35741/issn.0258-2724.56.3.31
|View full text |Cite
|
Sign up to set email alerts
|

Breadfruit-Based Starch Nanoparticles Prepared Using Nanoprecipitation to Stabilize a Pickering Emulsion

Abstract: This research describes the role of starch nanoparticles in stabilizing the surfactant-free emulsion, namely Pickering emulsion. However, the concentration of starch and NaOH during the preparation of starch nanoparticles as a Pickering emulsifier have not been studied. Thus, this study aimed to obtain the proper concentrations of starch and NaOH when preparing breadfruit-based starch nanoparticles as emulsifiers for a Pickering emulsion. This study varied the concentration of starch (1, 3,or 5 (%(w/v)) and Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 2 publications
0
6
0
2
Order By: Relevance
“…Breadfruit starch was obtained from wet-milled sediment of the Indonesian breadfruit. Then, breadfruit starch nanoparticle was produced using the nanoprecipitation method, as stated in Harsanto et al (2021); n-hexane, was purchased from MERCK, Germany. MCT oil was procured from PT.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Breadfruit starch was obtained from wet-milled sediment of the Indonesian breadfruit. Then, breadfruit starch nanoparticle was produced using the nanoprecipitation method, as stated in Harsanto et al (2021); n-hexane, was purchased from MERCK, Germany. MCT oil was procured from PT.…”
Section: Methodsmentioning
confidence: 99%
“…The 100 droplets observed using an optical microscope were measured for diameter using ImageRaster software (Informer Technologies, Inc.)., and the d 4,3 value was calculated based on Equation (3) (Li et al, 2013). could maintain the stability of Pickering emulsion for two weeks at room storage (Harsanto et al, 2021). Starch nanoparticles were observed to be adsorbed at the oil-water interface to stabilize the Pickering emulsion (Tan et al, 2014).…”
Section: Emulsion Propertiesmentioning
confidence: 99%
“…Moreover, the acid hydrolysis approach poses challenges to its implementation in industrial settings due to environmental concerns [169]. In recent years, alternative methods to obtain starch nanomaterials have been proposed, including physical treatments such as ultrasonication [157,170], stirred media milling [171], gamma radiation [172] and high-pressure homogenization [173,174]; enzymatic treatments [169]; nanoprecipitation in ethanol [175,176]; self-assembly methods; and combinations of methods such as acid hydrolysis with ultrasound [168,177], acid hydrolysis with precipitation [178], ball milling with acid hydrolysis [179], or enzymatic treatments with acid hydrolysis [180].…”
Section: Starch Nanomaterialsmentioning
confidence: 99%
“…Lu et al [123] also reported that the stability capacity of SNPs depends on the starch source, where normal corn starch showed a better stability compared with high-amylose starch. The concentration of starch used in the emulsion can increase the stability of emulsion associated with particles in the continuous phase, which increases the emulsion viscosity and thereby inhibits the separation of the emulsion phase and aggregation of oil droplets; as a result, the emulsion becomes more stable [118,124,125]. In addition to the concentration of added nanoparticles, emulsion stability can be affected by SNP type, size and hydrophobicity, where a small hydrophobicity contributes to increased emulsion stability [34,99,126].…”
Section: Pickering Emulsionmentioning
confidence: 99%